Material ilustrado como estratégia para envolvimento familiar e adesão ao uso do AASI em crianças com deficiência auditiva - Monteiro, Raquel Regina Rodrigues (2013)
caretakers of children with hearing loss that would foster their adherence to the use of HA and their understanding of the initial orientation regarding auditory and language abilities. The applicability of the use of such material with Public Hearing Health Care Service users was investigated. Method: The material development was based on the underlying principles observed in clinical appointments at Centro Audição na Criança, which subsidized the structure and content to be addressed. A version was made using the following steps: organization of a prototype, partnership with a graphic designer and virtual group discussion with the professionals involved. The applicability of the material was assessed by means of its use with parents and caretakers during the routine process of HA selection/adaptation, the early stages of therapy and follow up appointments with children with hearing loss. The subjects were: parents/ caretakers accompanying the patients, children whose HA would allow daily measures of use, and audiologists responsible for the therapy sessions with these subject children. For the analysis of the preliminary version of the material, the following steps were used: a script for registering applicability, measurements of average daily use of HA and interview guides for parents/ caretakers and audiologists. A brainstorming session with qualified professionals in the area of hearing loss was conducted to refine and collect ideas to inform the production of the final version of the illustrated material. Results: The preliminary version of the illustrated material was presented in A5 size booklet format with spiral binding. The booklet content addressed the following matters: HA handling and care, and orientation on hearing and oral language development. Participants of this study were: eight audiologists and 16 families, whose children s chronological age ranged between 6 (six) and 53 (fifty-three) months. The communication strategy of the contents was an interactive and pictographic one. As for adherence, many factors interfered in daily average use of HA. As for the general evaluation of the material, all parents/ caretakers considered it good and fifteen of them (93,75%) used it at home. All audiologists reported that the material addressed important issues of the early stages of HA adaptation and supported families and audiologists during the development process. The most frequently treated subjects were: adherence to use of HA (45%) and HA care (32%). The final version was prepared taking into account comments from parents, audiologists/ speech therapists who applied the preliminary version of the illustrated material and brainstorming results. Conclusion: The material was used at home by families and seemed to contribute to family involvement, since it expanded its influence to beyond the person accompanying the child to therapy sessions. The audiologists of the Public Hearing Health Care Service demonstrated good acceptance to the material because it has guided the rehabilitation process and was regarded as support both for the family and therapist. Adherence to HA use was heterogeneous among subjects and suffered interference from several factors during the HA process of adaptation. The use of the material can be considered as a facilitator in the communication process between families and therapist